PENGARUH HEALTH EDUCATION TERHADAP PENGETAHUAN DAN PERSEPSI PASIEN SEBELUM CAPSULE ENDOSKOPI DI RS PLUIT - Ezra Novyanauli, Utrecht; Dedi, Blacius; Mauliku, Novie E. (Jurnal Ilmiah Keperawatan IMELDA, 2024)
Background: Capsule endoscopy is a non-invasive diagnostic procedure to examine the upper digestive tract (small intestine). Capsule endoscopy examinations are still rarely performed by patients for various reasons. Therefore, it is necessary to increase knowledge and perception. The aim of this research is to determine the characteristics of respondents based on knowledge and perception Research Method: using a cross sectional design. The population in the study were all internal medicine patients at Pluit Hospital, totaling 36 samples. The research sample consisted of 36 people divided into 2 groups with a ratio of 18 respondents in the intervention group and 18 respondents who did not receive intervention or the control group. The research time was from May 2023 to January 2024 with side purpose sampling technique. The intervention carried out was providing education to the control group and instruments used to collect data using questionnaires. Data analysis was carried out univariately and bivariately using the Wilcoxon Test and the Mann - Whitney Test. Research Results: show that there is an influence of Health Education on patient knowledge and perceptions (p value 0.004). Conclusion: Providing Health Education can influence respondents' knowledge and perceptions about carrying out capsule Endoscopy examinations. The recommendation given is that patients should be given Health Education by medical personnel who are experts in each field, such as in this study, nurses who are experts and work in the diagnostic room..